Urological malignancy after renal transplantation. - Besarani, D; Cranston, D (2007)
Immunosuppression in solid-organ recipients is associated with a greater risk of de novo malignancy after transplantation; herein we report the UK transplant registry (UKTR) database of urological cancer after renal transplantation in the UK transplant population. From September 1999 to January 2006 there were 10,847 kidney recipients with at least one period of follow-up reported after a kidney transplant (mean age at transplantation 42.4 years, sd 15.5; 6685 male, 61.6%, and 4162 female, 38.3%). The recipients represent a homogenous group who received different immunosuppression regimens. Skin cancer was excluded from the study. Unfortunately, the UKTR does not collect information about the presence or absence of cancer, either at registration onto the transplant waiting list or at transplantation. In all, 214 (1.9%) patients were reported to have a subsequent urological malignancy diagnosed among the 10,847 recipients. The UKTR was used to identify patients who developed urological malignancies after renal transplantation, which is a challenging event after solid-organ transplantation. Regular surveillance to diagnose early occurrence and adjustment of immunosuppression might be beneficial. In the presence of metastatic disease, chemotherapy treatment with adjustment or cessation of immunosuppressive therapy is required.